Cysteinylation of a monoclonal antibody leads to its inactivation. Issue 4 (18th May 2016) - McSherry, Troy; McSherry, Jennifer; Ozaeta, Panfilo; Longenecker, Kenton; Ramsay, Carol; Fishpaugh, Jeffrey; Allen, Steven
ABSTRACT: Post-translational modifications can have a signification effect on antibody stability. A comprehensive approach is often required to best understand the underlying reasons the modification affects the antibody's potency or aggregation state. Monoclonal antibody 001 displayed significant variation in terms of potency, as defined by surface plasmon resonance testing (Biacore), from lot to lot independent of any observable aggregation or degradation, suggesting that a post-translational modification could be driving this variability. Analysis of different antibody lots using analytical hydrophobic interaction chromatography (HIC) uncovered multiple peaks of varying size. Electrospray ionization mass spectrometry (ESI-MS) indicated that the antibody contained a cysteinylation post-translational modification in complementarity-determining region (CDR) 3 of the antibody light chain. Fractionation of the antibody by HIC followed by ESI-MS and Biacore showed that the different peaks were antibody containing zero, one, or two cysteinylation modifications, and that the modification interferes with the ability of the modified antibody arm to bind antigen. Molecular modeling of the modified region shows that this oxidation of an unpaired cysteine in the antibody CDR would block a potential antigen binding pocket, suggesting an inhibition mechanism.